THE REALITY OF THE ECONOMIC EMPOWERMENT OF ALGERIAN WOMEN: ACCORDING TO INTERNATIONAL INDICATORS OF EMPOWERMENT - Dendougui, Dr. Soumia; Shlash Al-Mahdawi, PhD. Khalid Hussein; Trifa, Dr. Mohamed (The journal of contemporary issues in business and government, 2024)
This research paper aims to determine the level of economic empowerment of Algerian women according to international indicators. The study also seeks to answer the main question of whether Algeria has the potential to enhance the level of economic empowerment of Algerian women and whether there is a real and actual will to achieve economic empowerment. To address the subject of the study on the status of Algerian women and their place in work within Algerian society between what reality imposes and what it faces in terms of challenges, both the case study method and the institutional legal approach were used to identify the indicators of economic empowerment in addition to identifying the most important legislation and legal reforms. The study found that there is a contrast between what the legislation and laws stipulate, and the practice and implementation of plans and programs based on gender in accordance with the principle of equal opportunity. The study concluded that despite the government’s efforts to enact laws in accordance with the principle of equal opportunity, the reality proves that the efforts to economically empower Algerian women still have a long way to go to achieve this.